KANDUNGAN BAKTERI AIR SUNGAI MUSI SAAT PASANG DAN SURUT DI KOTA PALEMBANG - Novianti, Dewi (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2014)
Study bacterial content of the Musi river water at high tide and low tide in the city of Palembang was implemented in January through April 2014. Objective research to determine the water quality of the river Musi at high tide and low tide is based on the total number of bacteria and bacterial coliformnya. This study used a different test (T-test) consisting of 2 factors and 5 replications. Observation parameters consist of: the total number of bacterial colonies growing on media NA, and the number coliform test results obtained from the estimation and confirmation tests. The data obtained by different test T-test. The results of the calculation and analysis of the differences found in total bacterial counts at high tide and low tide, it appears that events tidal effect on the bacterial content in the water of the river Musi. Total content of more bacteria at low tide than at high tide. Key words: water river Musi, the total number of bacteria, and coliform bacteria